Mental capacity legislation in the UK: systematic review of the experiences of adults lacking capacity and their carers. (October 2017) - Wilson, Sam
Abstract : Aims and method: Capacity legislation in the UK allows substitute decision-making for adults lacking capacity. Research has explored the experiences of such adults and their carers in relation to the Adults with Incapacity (Scotland) Act 2000, and the Mental Capacity Act 2005 in England and Wales. A systematic review of the relevant research was performed using a framework method. Results: The legislation provided mechanisms for substitute decision-making which were seen as useful, but there were negative experiences. Decision-making did not always seem to follow the legislative principles. Awareness of the legislation was limited. Most research was qualitative and some was of low methodological quality. Data were too heterogeneous to allow comparisons between English and Scottish law. Clinical implications: Capacity legislation was generally viewed positively. However, some experiences were perceived negatively, and the potential benefits of the legislation were not always utilised.